The Red and Blue Effect: Predicting New International Students by 2016 U.S. Presidential Election Outcomes (Higher Education Politics and Economics, 2023)
For the first time in U.S. higher education history, new international student enrollment at four-year U.S. institutions declined for the second consecutive academic year in 2017-2018. Many studies have investigated why international students choose to pursue U.S. higher education. However, scant research has explored how U.S. politics affects the number of new international students studying in the U.S. We explore whether there was a “red effect” (Republican counties) or a “blue effect” (Democratic counties) experiencing declines in international student enrollment. Using institutional-level fixed effects approaches, new international student enrollment declined at many institutions in Republican-voting counties, while new international student enrollment remained steady or increased at institutions in Democratic-voting counties. Implications for research, practice, and international education are addressed.